Derived neutrophil by lymphocytes ratio is a misnomer, implication of derived leucocytes ratio in diagnosing gastric cancers - P. G., Naveen; Karanth, K. Veena L. (International Surgery Journal, 2018)
Background: Gastric malignant neoplasms are well-known common malignant disease seen in routine clinical practice. In India incidence are comparatively low but accounts for significant mortality and morbidity. Gastric malignancy incidence adds significant numbers every year to cancer related deaths worldwide. And prognosis is not satisfactory in spite of medical innovations and technological advancements. Early diagnosis helps for successful surgical removal of gastric cancer and to achieve a curative resections. Present study objectives are to solve the paradox of misnomer derived neutrophil by lymphocyte ratio and to evaluate statistical differences of blood leucocyte parameters in patients with gastric malignancies as compared to control cases and its application as screening markers in diagnosing gastric cancers. Methods: Hundred cases of gastric malignancy and hundred controls-age, gender matched to cases without malignancy or infection were included. Both groups evaluated with routine complete blood count and upper GI endoscopy reports, Data regarding WBC counts, neutrophil counts, lymphocyte counts, monocytes, eosinophils and basophils were noted and Derived Leucocytes Ratio (DLR) were calculated and compared to look for statistical differences. Results: Hematological leucocyte parameters revealed statistical differences in gastric cancer patients in comparison to controls. Neutrophils were increased and lymphocytes decreased with elevated DLR levels. Conclusions: Leucocyte parameters like neutrophils and lymphocytes shows varying trends in gastric cancer and elevated derived leucocytes ratio can be utilized as a screening marker in Gastric cancers.